New Horizons and Prospects in Oral Cancer Detection - Ojha Ayushi; Panda Baisali; Mishra Pallavi; Das Duttatrayee; Kumar Vijay; Bhuyan Lipsa (Wolters Kluwer Medknow Publications, 2024)
Recent advancements in oral cancer detection prioritize non-invasive and minimally invasive techniques for efficient and accurate screening. This review outlines progress in methods such as narrow band imaging, fluorescence imaging, and optical coherence tomography, showing promise in early lesion detection. Biomarker detection in saliva and targeted nanoparticles enhance early diagnosis, while machine learning improves diagnostic accuracy. However, clinical validation and large-scale studies are needed for widespread adoption.